Oil Extraction from Macrophytes: Effect of Environmental Factors on Efficiency and Oil Quality in Coastal Lagoon - Renzi, Monia; Scirocco, Tommaso; Cilenti, Lucrezia; Bastianoni, Simone; Specchiulli, Antonietta (Journal of Environmental Accounting and Management, 2026)
Macrophytes represent interesting matrices for oil extraction with biodiesel production purposes, particularly in eutrophic coastal lagoons. This short note reported results on bio-oil extraction efficiency in two different species of macrophytes in a Mediterranean lagoon (Lesina lagoon, south-eastern Italy), by testing effects of different factors (year, season, species of macrophytes) on oil production and oil quality. Extracted total oils values ranged from 0.65 % (Chara spp.) to 2.35 % (Chaetomorpha linum) and a significant difference (p